2019
DOI: 10.1108/jes-07-2017-0181
|View full text |Cite
|
Sign up to set email alerts
|

Real exchange rate misalignment and economy

Abstract: Purpose The purpose of this paper is to examine the impact of real exchange rate misalignment on economy and economic sectors, namely construction, manufacturing and mining and quarrying in Malaysia. Design/methodology/approach The equilibrium real exchange rate and economic models are estimated using the autoregressive distributed lag approach. Findings An increase in productivity differential or reserve differential will lead to an appreciation of real exchange rate in the long run. An increase in positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…RER misalignment is extensive in fixed exchange rate regime but transitory in a flexible exchange rate regime (Wong, 2019). The reason is that in a flexible regime market forces bring RER back to the equilibrium level immediately which is not in the case under fixed exchange rate regime.…”
Section: Literature Reviewmentioning
confidence: 96%
“…RER misalignment is extensive in fixed exchange rate regime but transitory in a flexible exchange rate regime (Wong, 2019). The reason is that in a flexible regime market forces bring RER back to the equilibrium level immediately which is not in the case under fixed exchange rate regime.…”
Section: Literature Reviewmentioning
confidence: 96%
“…( 3) and ( 4) are, respectively, 𝐻𝐻 0 : 2020) has demonstrated that estimates of 𝛹𝛹 1 and 𝜂𝜂 1 are exactly the same as the estimates of the coefficients attached to lagged error-correction terms due to Engle and Granger (1987). Wong (2019) and Shin et al (2014) in decomposing the 𝑀𝑀𝑀𝑀𝑀𝑀variable into positive changes denoted by ∆𝑀𝑀𝑀𝑀𝑀𝑀 + and negative changes, denoted by ∆𝑀𝑀𝑀𝑀𝑀𝑀 − .In our case, given the adopted definition of 𝑅𝑅𝐸𝐸, negative values reflect an undervaluation of the dollar against the renminbi (renminbi overvalued) and positive values indicate an overvaluation of the dollar against the renminbi (renminbi undervalued).…”
Section: Ii-econometric Methodologymentioning
confidence: 92%
“…Another common feature of prior studies is that they have mainly relied on aggregate trade data, which means that may suffer from the well-known aggregation bias problem. Indeed, as pointed out by Wong (2019), different industries may react differently to RE misalignment, depending on industry-specific factors such as the industry structure, the demand and supply elasticity, the firm heterogeneity, and the product quality (Melitz and Redding, 2014).Therefore, we consider in this paper commodity-level trade flows between the United Statesand China and assess the possible symmetric as well as asymmetric effects of RE misalignment on the exports and imports of 66 commodities that trade between the two investigated countries. For this purpose, we make use of two recent econometric techniques, namely the symmetric (linear) ARDL approach of Pesaran et al (2001) and the asymmetric nonlinear ARDL approach of Shin et al (2014).…”
Section: I-introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fornero et al (2020) focused on the case of Chile, concluding that the influence of foreign demand on manufacturing exports was stronger than those arising from the exchange rate change. Wong (2019) contributes to the research of the effects of exchange rate misalignments, using autoregressive distibuted lag (ARDL) approach on the example of Malaysia, concluding that undervaluation has a positive impact on manufacturing sector. Inversely, influence of overvaluation is proven to be negative.…”
Section: Literature Overviewmentioning
confidence: 99%